2020
DOI: 10.1111/obr.13155
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between IgA and gut microbiota and its role in controlling metabolic syndrome

Abstract: Summary Immunoglobulin A (IgA) is the most abundant immunoglobulin isotype secreted into the mucosal tissues, mainly intestinal mucus. Humans can produce several grams of IgA every day, accounting for three quarters of the body's total immunoglobulin content. IgA, together with mucus and antimicrobial peptides, forms the first line of defence for intestinal epithelial cells, protecting them from a significant number of intestinal antigens. IgA also plays a principal role in controlling the gut microbiota (GM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 148 publications
(539 reference statements)
1
22
0
1
Order By: Relevance
“…A similar trend was evident for the antigens from the feces of P mice compared to the LDP mice but did not reach signi cance (P = 0.094). Moreover, the mRNA expression of the Jchain and IL-6 of the ileum tissue was also higher, while tumor necrosis factor (ligand) superfamily, member 13 (also known as APRIL) and 13b (also known as BAFF) were not in uenced, when cultured with antigens derived from the feces of Ctr and F mice than those from the LDP mice (Figure 3B), suggesting that Ctr and F antigens may increase IgA production through enhancing the survival and activity of IgA+ PCs 19 .…”
Section: The Inhibition Of Intestinal Iga Response By Ldp Was Gm-and Early Life-dependentmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar trend was evident for the antigens from the feces of P mice compared to the LDP mice but did not reach signi cance (P = 0.094). Moreover, the mRNA expression of the Jchain and IL-6 of the ileum tissue was also higher, while tumor necrosis factor (ligand) superfamily, member 13 (also known as APRIL) and 13b (also known as BAFF) were not in uenced, when cultured with antigens derived from the feces of Ctr and F mice than those from the LDP mice (Figure 3B), suggesting that Ctr and F antigens may increase IgA production through enhancing the survival and activity of IgA+ PCs 19 .…”
Section: The Inhibition Of Intestinal Iga Response By Ldp Was Gm-and Early Life-dependentmentioning
confidence: 99%
“…Early-life high-dose antibiotic treatment has been shown to transiently inhibit the intestinal IgA response in mice [17][18] . As intestinal SIgA is closely related to the development of MetS 21 , we then sought to determine the in uence of early-life LDP on intestinal IgA response. There were no signi cant difference in the fecal SIgA among all 14 d and 21 d age of mice, suggesting that the passive SIgA received from their mothers via breast milk was not in uenced by LDP (Figure S2A).…”
Section: Ldp Treatment Persistently Dampened Intestinal Iga Responsementioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that promoting factors of IgA secretion are decreased in high-fat-diet (HFD)-fed mice [ 22 ]. Another paper suggested that IgA secretion may be inhibited in the context of low-grade inflammation and metabolic syndrome in obese humans and mice [ 23 ]. However, most reviews on diabetes and immunity do not discuss humoral immunity, including IgA responses [ 24 ].…”
Section: Introductionmentioning
confidence: 99%